INTRODUCTION OF HEALTH-IMPROVING PRODUCTS IN RESTAURANTS - Лакома, Екатерина; Сильчук, Татьяна (SWorldJournal, 2021)
The positive trend of healthy eating is gaining momentum. Therefore, the requirements for modern nutrition contribute to the expansion of the range of confectionery, in particular in restaurants. The menu of health-improving purpose in cafe-confectionery